The Pandemic and Its Mitigation Efforts in the Qur'ān (A Study of the Interpretation of Nawawī al-Bantanī in Tafsīr Marāḥ Labīdh) - Rosyida, Hanik; Jamil, M. Mukhsin; Ghofur, Abdul; Masruri, Ulin Niam (Millati: Journal of Islamic Studies and Humanities, 2022)
This study comes from the wide and huge effect of the pandemic Covid-19 in almost all aspects of human life. The over-reaction and various responses from society bring polemic in mitigation works that the number of infected patients by Covid-19 virus raise from time to time. Islam has actually paid attention to the problem of pandemics and epidemics as explained in the Qur’an and Hadith. On the other hand, Indonesian Muslim society has a strong tendency to the Qur’an as the main source of life teaching and guidance. Therefore, the interpretation on Qur’anic verses related to pandemic mitigation in the book of Tafsīr Nusantara, that is Tafsīr Marāḥ Labīdh written by Syaikh Nawawī al-Bantanī and its relevance in the present context. This is a qualitative study that uses the inductive method and contextual approach to explain the interpretation. At last, this study infers some conclusions. First, Syaikh Nawawī sees the pandemics and epidemics as the examination and test (muṣībah) from Allah SWT to all humankind. Second, Syaikh Nawawī explains that the Qur’ān orders humans to be alert to the coming pandemic and plague in the same manner as the act of facing the coming of enemies in war.